A study of m-N-extremally Disconnected Spaces With Respect to, Maximum mX-N-open Sets - Salih, Ahmed A.; Ali, Haider J. (Iraqi Journal of Science, 2021)
The aim of this research is to prove the idea of maximum mX-N-open set, m-N-extremally disconnected with respect to t and provide some definitions by utilizing the idea of mX-N-open sets. Some properties of these sets are studied.